LITERATURE AS A SOURCE OF TRADITIONAL KNOWLEDGE: THE ECOCRITICAL STUDY OF BALI AGA FOLKLORE - Ida Ayu Laksmita Sari (International Journal of Research Science and Management, 2018)
The Bali Aga community has many folktales that are still known until nowadays. More than just a tale for entertainment or solace, the stories told from generation to generation also convey moral teachings and life advice. This paper analyzed the Balinese Aga folklore by identifying the traditional knowledge contained in it. The object of the research is the folklore of Bali Aga collected in the book Ceritera Rakyat Bali: Desa Tenganan, Pedawa, Tigawasa (1987). The focus of the analysis is on the forms and benefits of traditional knowledge contained in the story, especially those relating to living livelihoods and those that are useful for preserving nature. The text is analyzed using ecocritical studies, an approach that analyzes literary texts with a multidisciplinary environmental approach. This paper concludes that Balinese folklore contains a lot of traditional knowledge that people live and practice as skills for livelihoods and maintain their harmonious relationship with nature.